2021
DOI: 10.3892/br.2021.1454
|View full text |Cite
|
Sign up to set email alerts
|

Promoter polymorphism of TNF‑α (rs1800629) is associated with ischemic stroke susceptibility in a southern Thai population

Abstract: Stroke represents the leading cause of disability and mortality amongst the elderly worldwide. Multiple risk factors, including both genetic and non-genetic components, as well as their interactions, are proposed as etiological factors involved in the development of ischemic stroke (IS). Promoter polymorphisms of the IL-6-174G/C (rs1800795) and TNF-α-308G/A (rs1800629) genes have been considered as predictive risk factors of IS; however, these have not yet been evaluated in a Thai population. The aims of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…González-Navarro et al, 2020), ischaemic heart disease (Kamdee et al, 2021) and diabetes (Shi et al, 2021). The literature highlights an association between the A allele in the rs1800629 variation in TNF-⍺ as a protective factor to diseases related to bone metabolism, such as acute AP, osteoporosis, and bone fracture risk (Amaya et al, 2013;de Sá et al, 2007;Jin et al, 2018;Kotrych et al, 2016;Moffett et al, 2005), data that corroborate with the results observed in the present study. Shi et al (2021) reported in a review article a higher risk for developing periodontal disease in Asian diabetic patients related to rs1800629 variation in TNF-⍺, which may be related to higher levels of TNF-⍺, although the study reports that such data are still inconclusive in the literature.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…González-Navarro et al, 2020), ischaemic heart disease (Kamdee et al, 2021) and diabetes (Shi et al, 2021). The literature highlights an association between the A allele in the rs1800629 variation in TNF-⍺ as a protective factor to diseases related to bone metabolism, such as acute AP, osteoporosis, and bone fracture risk (Amaya et al, 2013;de Sá et al, 2007;Jin et al, 2018;Kotrych et al, 2016;Moffett et al, 2005), data that corroborate with the results observed in the present study. Shi et al (2021) reported in a review article a higher risk for developing periodontal disease in Asian diabetic patients related to rs1800629 variation in TNF-⍺, which may be related to higher levels of TNF-⍺, although the study reports that such data are still inconclusive in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the gene for TNF-α is highly polymorphic with many polymorphisms. The rs1800629 gene polymorphism has already been evaluated in relation to bone diseases, temporomandibular disorders, periodontal diseases, autoimmune diseases (Jin et al, 2018;Kotrych et al, 2016;Moffett et al, 2005;Shi et al, 2021) and with Herpesviruses infection (Jakovljevic et al, 2020;Wu et al, 2002). It is important to emphasize here that TNF-⍺ is a well-known pleiotropic gene, in which the same gene or genetic variant has an effect in different traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strictly following the inclusion criteria, 47 properly controlled full-length studies, including 23 rs1800629 genotype-related studies ( Um et al, 2003 ; Balding et al, 2004 ; Lee et al, 2004 ; Um and Kim, 2004 ; Karahan et al, 2005 ; Rubattu et al, 2005 ; Harcos et al, 2006 ; Lalouschek et al, 2006 ; Llamas Sillero et al, 2007 ; Banerjee et al, 2008 ; Shi et al, 2009 ; Kim et al, 2010 ; Tong et al, 2010 ; Sultana et al, 2011 ; Cui et al, 2012 ; Tuttolomondo et al, 2012 ; Zhao et al, 2012 ; Djordjevic et al, 2013 ; Wawrzynek et al, 2014 ; Gu et al, 2015 ; Kumar et al, 2016 ; Palm et al, 2020 ; Kamdee et al, 2021 ) and 13 case reports ( Zaremba and Losy, 2001a , b ; Intiso et al, 2004 ; Domac et al, 2007 ; Jefferis et al, 2009 ; Cure et al, 2013 ; Bokhari et al, 2014 ; de Sousa Parreira et al, 2015 ; Wytrykowska et al, 2016 ; Billinger et al, 2017 ; Shishkova et al, 2018 ; Zhang Y. Y. et al, 2018 ; Ma et al, 2020 ) on the circulating level of TNF-α were finally selected for the meta-analysis ( Figure 1 ). Genotype-related literature included a total of 9,120 patients and 9,249 healthy controls (Caucasian, n = 10; Asian, n = 15).…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that these studies are still controversial regarding methodological and sampling variables, from the point of view of disease, treatment, and ethnic and individual factors (14,130). The pleiotropic effect of genetic polymorphisms may explain part of the associations observed in epidemiological studies between AP and different systemic alterations, such as metabolic syndrome (131,132), ischemic heart disease (133) and diabetes (134). Additionally, a recent review emphasized the need for further studies within new cohorts of different populations and ethnicities to either confirm or refute the role of genetic polymorphisms in AP (135).…”
Section: Influence Of Genetic Polymorphisms On Apical Periodontitis R...mentioning
confidence: 99%